Analisis Gaya Kepemimpinan Perempuan Bupati Tabanan Periode 2010-2020 - Devia Devi, Luh Mutiara; Yudartha, Putu Dharmanu; Purnamaningsih, Putu Eka (CITIZEN CHARTER, 2019)
zABSTRACTz Putu Eka Wiryastuti was the first female regent in Bali to lead Tabanan for two periods. The purpose of research that is to be achieved is to know the leadership style of Putu Eka Wiryastuti as the female leader in Tabanan Regency period 2010-2020. This research uses a qualitative method of exploratory with data collection techniques in the form of interviews, observations and documentation. Leadership styles are generally divided into authoritarian, democratic and laissez-faire leadership styles. While the distinctive style of women leadership is divided into masculine-feminine and transactional-transformational styles. The results of this research show that the leadership style that was applied by Putu Eka Wiryastuti as the female leader in Tabanan Regency in 2010-2020 period generally more in accordance with the approach of Democcentric leadership with objective features and Women's distinctive leadership style that is more in line with a feminine-transactional approach with a cooperative trait. Keywords:Leadership style, Tabanan Regency Government, Typical women leadership